Boas práticas de governança de gestão de pessoas: capacitação de servidores em cargo de chefia e com foco na saúde mental - Surek, Anelise de Fatima Dzieciol (2023)
This study seeks to develop a training proposal for managers and employees involved in situations of mental disorders, aiming at the formation of good governance practices for people management in health care and surveillance in Federal Higher Education institutions. Considering that mental health appears as one of the main causes of absences of public servants due to health problems, it is necessary to raise awareness among managers/heads of departments about good governance practices that take into account the specific needs of civil servants with health problems mental. The research was carried out in unit 323 of the Integrated Public Health Care System (SIASS), which has campuses located in 37 cities in the state of Paraná. The methodology used was descriptive and qualitative research. For the descriptive research, primary data was collected from the system that specifically takes care of the server’s health. Qualitative research was carried out through interviews with public servants who carry out leadership roles in different areas, aged between 25 and 75 years and who have employees on their team who have mental health disorders/problems. At the end of the study, a training proposal for managers or employees was prepared involved with situations of mental disorders, as support for care, surveillance and health promotion, thus establishing an innovation in governance, as governance must be understood as a system of relationships between institutions, organizations and individuals só that innovations can be made viable.